Plastid Genomes of Five Species of Riverweeds (Podostemaceae): Structural Organization and Comparative Analysis in Malpighiales - Bedoya, Ana M.; Ruhfel, Bradley R.; Philbrick, C. Thomas; Madriñán, Santiago; Bove, Claudia P.; Mesterházy, Attila; Olmstead, Richard G. (Frontiers in Plant Science, 2019)
With the advent of next generation sequencing technologies, whole plastome data can be obtained as a byproduct of low coverage sequencing of the plant genomic DNA. This provides an opportunity to study plastid evolution across groups, as well as testing phylogenetic relationships among taxa. Within the order Malpighiales (~16,000 spp.), the Podostemaceae (~300 spp.) stand out for their unique habit, living attached to rocks in fast-flowing aquatic habitats, and displaying highly modified morphologies that confound our understanding of their classification, biology and evolution. In this study, we used genome skimming data to assemble the full plastid genome of five species within Podostemaceae. We analyzed our data in a comparative framework within Malpighiales to determine the structure, gene content and rearrangements in the plastomes of the family. The Podostemaceae have the smallest plastid genome reported so far for the Malpighiales, possibly due to variation in length of IR regions, gene loss, and intergenic region variation. We also detected a major inversion in the large single copy region unique to the family. The uncommon loss or pseudogenization of ycf1 and ycf2 in land plants is also found to be characteristic of Podostemaceae, but the compensatory mechanisms and implications of this and of the pseudogenization of accD, rpl22 and clpP, and loss of rps16 remain to be explained in this group. In addition, we estimated a phylogenetic tree among selected species in Malpighiales. Our findings indicate that the Podostemaceae are a distinct lineage with long branches that suggest faster rates of evolution in the plastome of the group, compared to other taxa in the order. This study lays the foundations for future phylogenomic studies in the family.